2020
DOI: 10.1073/pnas.1911444117
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mutagenesis of a GPCR ligand: Detoxifying “inflammo-attraction” to direct therapeutic stem cell migration

Abstract: A transplanted stem cell’s engagement with a pathologic niche is the first step in its restoring homeostasis to that site. Inflammatory chemokines are constitutively produced in such a niche; their binding to receptors on the stem cell helps direct that cell’s “pathotropism.” Neural stem cells (NSCs), which express CXCR4, migrate to sites of CNS injury or degeneration in part because astrocytes and vasculature produce the inflammatory chemokine CXCL12. Binding of CXCL12 to CXCR4 (a G protein-coupled receptor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
(152 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, to counter this side effect, one preclinical study implanted human NSC derived from human induced pluripotent stem cells (iPSC)-NSC (discussed in section: iPSC-NSC) in mouse brains pretreated with a mutated form of the SDF1 ligand (termed SDV1a) prior to implantation. Interestingly, the SDV1a pretreatment promoted the migration of transplanted NSC to the site of injury without promoting inflammation [41].…”
Section: Vascular Endothelial Cell Regulation Of Nscmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, to counter this side effect, one preclinical study implanted human NSC derived from human induced pluripotent stem cells (iPSC)-NSC (discussed in section: iPSC-NSC) in mouse brains pretreated with a mutated form of the SDF1 ligand (termed SDV1a) prior to implantation. Interestingly, the SDV1a pretreatment promoted the migration of transplanted NSC to the site of injury without promoting inflammation [41].…”
Section: Vascular Endothelial Cell Regulation Of Nscmentioning
confidence: 99%
“…In contrast, the noncanonical Notch ligand, EGFL7 known as an inhibitor of JAG-1-induced Notch signaling, acts as a neurovascular regulator of SVZ-NSC controlling olfactory perception and behavior [25]. Another study conducted in middle cerebral artery occlusion stroke-induced mice, reported that stroke enhances the SVZ's BBB 'leakiness' to facilitate direct access to stroke-induced increased levels of VEGF-A 165 to niche cells [41]. Additionally, these authors reported that the increase in VEGF-A levels post stroke activates Notch signaling by a transient induction of the Notch ligand DLL4 mRNA levels to enhance SVZ neurogenesis post stroke [27].…”
Section: Vascular Endothelial Cell Regulation Of Nscmentioning
confidence: 99%
“…NSCs can migrate to areas of injury and neurodegeneration in the CNS. Migration and engagement of NSCs with a pathologic niche is the first step in cell-mediated restoration of homeostasis to the injured region [ 18 , 76 , 77 , 78 , 79 ]. NSC pathotropism, which is the natural tendency of homing to the site of injury, is partly achieved by chemokine receptors on NSCs that respond to proinflammatory cytokines secreted from the pathologic region [ 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Biology Of Neural Stem Cellsmentioning
confidence: 99%
“…NSC pathotropism, which is the natural tendency of homing to the site of injury, is partly achieved by chemokine receptors on NSCs that respond to proinflammatory cytokines secreted from the pathologic region [ 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. For example, chemokine stromal cell-derived factor-1α (SDF-1α/CXCL12) interacts with CXCR4 receptors on NSCs as a major step in directing NSCs to injured brain regions [ 74 , 76 , 83 , 87 ]. The role of SDF-1α in stem cell homing is also implicated in cardiovascular and renal disease [ 88 , 89 , 90 ].…”
Section: Biology Of Neural Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation